Sentidos construídos sobre o trabalho por pessoas idosas no contexto da Covid-19 - Miguel, Maria das Graças Duarte (2024)
Introduction: work activity for an elderly person has a social and emotional meaning that is essential to life, in particular, in the exercise of their profession, capable of having a positive impact on promoting active and healthy aging. Objectives: to identify the dimensions of social representations about work constructed by elderly people during the social isolation imposed by the Covid-19 pandemic; understand social representations about remote work associated with work activities during the period of social isolation; compare the social representations about work and remote work constructed by elderly people. Method: this is an exploratory study with a qualitative approach, carried out at the Instituto Paraibano de Envelhecimento, at the Federal University of Paraíba, with fifty elderly people, active or retired. To collect the data, the following were used: free word association, with the inducing term: “work for elderly people”; and questions about: work and remote work. The data were organized into two textual corpus and analyzed with the help of the IRaMuTeQ software and interpreted based on the dimensions of the theory of social representations. Results: the fifty elderly people who participated were women, aged between 60 and 79 years; Most of them are married and have completed higher education and in the following professions: teachers, administrative technicians and administrative assistants. The results of the first corpus (contents of free word association) indicated three semantic classes: class one - socio-cognitive dimensions of work, exemplified by segments of texts in which work is pointed out as a source of personal fulfillment, continuous growth, emotional well-being , exchange of knowledge and affection; class two - socio-affective dimensions of work: formed by segments of texts in which elderly people talk about their emotions, the importance of work for empowerment, dedication and talk about emotional aspects about work and, class three - practical-functional dimensions: pointed out content in which elderly people talk about the importance of work in everyday life: aspects that promote socialization, continuous learning, financial independence, pleasure and freedom. The analysis of the contents of the second corpus revealed three semantic classes: the first class - psychosocial dimension of remote work, formed by speech segments in which elderly people describe both their daily work before the pandemic and highlight remote work, considering it o a great challenge, to be overcome, in particular, in the process of adapting to new technologies, essential to remain productive; class two: adaptation and technological challenges, includes words related to learning, adaptation and use of technologies to perform remote work. In class three: made up of segments of texts containing information about health and well-being in the pandemic in which older people are concerned about physical and mental health, management of chronic conditions and the importance of staying informed about the pandemic. Final considerations: the study highlights social representations about work for elderly people during the social isolation imposed by the Covid-19 pandemic, which are important to understand the impact of remote work for elderly people in work activity based on social representations about remote work. Elderly people highlight the importance of work in their lives, both as a source of financial independence and socialization. They highlight a concern with the Covid-19 pandemic about the importance of promoting digital inclusion and psychological support, creating adaptable and inclusive work environments.